Erythrocyte sedimentation rate as a marker for coronary heart disease - Yayan, Josef (Dove Medical Press, 2012)
BACKGROUND: Patients with angina pectoris or myocardial infarction frequently present without evidence of cardiac-specific heart enzymes by laboratory analysis or specific pathologic electro-cardiogram findings. The current study analyzed the efficacy of the erythrocyte sedimentation rate as an additional potential indicator for coronary heart disease, the aim being to enable quicker identification of patients with angina pectoris or myocardial infarction so that they can be more rapidly treated. METHODS: Patients with angina pectoris or myocardial infarction who had undergone a heart catheter examination were included in the study. The diagnosis of acute coronary heart disease was made by the physician who performed coronary angiography. Patients without coronary heart disease were used as a control group. The erythrocyte sedimentation rate was measured in all patients. Patients with angina pectoris or myocardial infarction and an inflammatory or tumor disease were excluded. RESULTS: The erythrocyte sedimentation rate was prolonged in 79 (58.09%) of 136 patients; 69 (50.74%) patients (95% confidence interval ±8.4%, 42.34%–59.14%) had coronary heart disease and a prolonged erythrocyte sedimentation rate. The erythrocyte sedimentation rate was prolonged in ten (7.35%) patients (95% confidence interval ±4.39%, 2.96%–11.74%) without coronary heart disease by coronary angiography. The specificity of the erythrocyte sedimentation rate for coronary heart disease was 70.59% and the sensitivity was 67.65%. CONCLUSION: Erythrocyte sedimentation rate may be a useful additional diagnostic criterion for coronary heart disease.